2009
DOI: 10.1590/s0004-282x2009000300008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and impact of headache and migraine among Brazilian Tupiniquim natives

Abstract: -This is the first study to evaluate the prevalence of headache and migraine among Tupiniquim Brazilian natives. A high prevalence of headache was found and the most prevalent headache was migraine. Women were more commonly affected than men. A high impact of headache was found, especially among migraineurs. Half of the headache sufferers were under medical assistance for headache given by the government Family Health Program (PSF). Most of them declared to use common analgesics. None of them was taking prophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…Regarding gender, female subjects have higher rates of migraine than male subjects, which is widely supported in the literature, 1 and occurs in many different settings. [18][19][20] We also found that job status was significantly associated with migraine. This type of association is described in the literature with contradictory results.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Regarding gender, female subjects have higher rates of migraine than male subjects, which is widely supported in the literature, 1 and occurs in many different settings. [18][19][20] We also found that job status was significantly associated with migraine. This type of association is described in the literature with contradictory results.…”
Section: Discussionsupporting
confidence: 55%
“…After controlling for confounding variables, migraine was associated with gender (female) and job status (employment). Regarding gender, female subjects have higher rates of migraine than male subjects, which is widely supported in the literature, 1 and occurs in many different settings 18‐20 …”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Migraine is a common and disabling primary headache disorder [1][2][3] . It has been reported that alcohol ingestion may trigger headache attacks in patients with migraine and tension type headache [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…The studies on headache prevalence in Brazilian Indians are scanty. Domingues et al studied a Tupiniquim Indian population (Aracruz, ES, Brazil) and found that the 6‐month headache prevalence was 65.2%; among those with headache, 47.8% of the women and 21.2% of the men were suffering from migraine.…”
Section: Headache In the Indian Populationmentioning
confidence: 99%